Countermeasures to Avoid Noncooperation in Fully Self-Organized VANETs - Jezabel Molina-Gil; Pino Caballero-Gil; Cándido Caballero-Gil (The Scientific World Journal)
The secure and efficient exchange of information in vehicular ad hoc networks (VANETs) involves more challenges than in any other type of ad hoc networks. This paper proposes a new vehicular communication system based on mobile phones for fully distributed and decentralized networks. In these networks, communications depend on individual nodes, which could decrease the efficiency and reliability of transmitted information. Besides, the limitation in the resources of mobile devices is an additional obstacle in the forwarding problem, and the content of the information generated by individual nodes must be considered inherently unreliable. In particular, this paper proposes the application of groups as a basis structure for a cooperation mechanism useful in event generation and in packet retransmission. Its aim is to promote the involvement of nodes in network performance. Given that such participation involves consumption of node resources, a group-based structure is here used not only to reduce communication overload but also to prevent sending false information and to encourage nodes in relaying packets. Several simulations of the proposal have been done, and the results have confirmed that this is a promising approach to increase network efficiency and trust in transmitted information, while reducing the number of selfish nodes in VANETs.